2009
DOI: 10.1007/s00005-009-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

CD40-activated B cells from patients with systemic lupus erythematosus can be modulated by therapeutic immunoglobulins in vitro

Abstract: Introduction: Aberrant signaling within and between B and T cells, considered to be central in systemic lupus erythematosus (SLE), could depend on enhanced CD40-CD154 activation. As a result, autoreactive B cells, normally anergic, differentiate and secrete antibodies attacking several normal tissues. Thus restorating B cell homeostasis might help control this disease. In this study, two facets of SLE B cells were investigated, namely their in vitro response to CD40-CD154 and the effect of treatment with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 64 publications
3
13
0
Order By: Relevance
“…Our data are in line with studies showing that IVIg stimulates B cells [54] and CD4+ T cells in vivo and in vitro [54, 55], and increased in vitro secretion of IgG [56, 57] that were highly reactive against human IgG F(ab') 2 fragments [57]. Importantly, Fab fragments isolated from one Kawasaki patient before and after IVIg treatment revealed that they displayed a higher affinity for IVIg after therapy [58].…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with studies showing that IVIg stimulates B cells [54] and CD4+ T cells in vivo and in vitro [54, 55], and increased in vitro secretion of IgG [56, 57] that were highly reactive against human IgG F(ab') 2 fragments [57]. Importantly, Fab fragments isolated from one Kawasaki patient before and after IVIg treatment revealed that they displayed a higher affinity for IVIg after therapy [58].…”
Section: Discussionsupporting
confidence: 92%
“…Rather, our results showed that IVIg indirectly inhibited the in vivo and in vitro T cell responses by impairing antigen presentation. Similarly, Néron et al showed that IVIg did not inhibit immunoglobulin secretion by human B cells activated by CD154 (the ligand for CD40) in the presence of cytokines such as IL-2, IL-4 and IL-10 [30], in contrast to the previously reported effects observed using PWM to stimulate B cells in the presence of IVIg [11,22,25]. Another recent report also showed the absence of a direct effect of IVIg on B cells [27].…”
Section: Discussionmentioning
confidence: 91%
“…Paradoxically, IVIG increased plasma cell differentiation and IgG production in an in vitro model where B cells were cultured on a layer of CD40L‐expressing fibroblasts in the presence of IL‐4 and IL‐10 . Importantly, B cells from patients with SLE cultured in the same model were also driven to increase plasma cell differentiation in the presence of IVIG . To explain this surprising effect, which could contribute to the development of an autoimmune disease instead of limiting it, the authors proposed that IVIG promotes differentiation of newly formed plasma cells that enter into competition with the already present autoreactive plasma cells.…”
Section: Modulation Of Plasma Cell Differentiation and Ig Productionmentioning
confidence: 99%